Hybrid anisotropic materials for wind power turbine blades - Golfman, Yosif (Boca Raton, Fla. : CRC Press, 2012)
'Exploring a wide range of key technical topics, this book presents up-to-date coverage of anisotropic materials used in the production of turbine blades. The text presents important information in the materials selection of carbon/fiberglass, the percentage combinations, and the design concepts required for manufacturing wind blades. The author presents the strength criteria for anisotropic materials, as well as the manufacturing criteria for turbine blade materials selection. In addition, this comprehensive resource also examines dynamic fatigue life factors in turbine blade design. Other topics include NDE methods for predicting deflections, stiffness, and strength'--
Includes bibliographical references and index.
Keywords: Turbines -- Blades -- Materials; Wind turbines -- Materials; Anisotropy